Research progress on detection techniques for point-of-care testing of foodborne pathogens - Liu, Sha; Zhao, Kaixuan; Huang, Meiyuan; Zeng, Meimei; Deng, Yan; Li, Song; Chen, Hui; Li, Wen; Chen, Zhu (Frontiers in Bioengineering and Biotechnology, 2022)
The global burden of foodborne disease is enormous and foodborne pathogens are the leading cause of human illnesses. Detection of foodborne pathogenic bacteria has become a research hotspot in recent years. Rapid detection methods based on immunoassay, molecular biology, microfluidic chip, metabolism, biosensor and mass spectrometry have developed rapidly and become the main methods for detection of foodborne pathogens. This paper reviewed a variety of rapid detection methods in recent years. The research advances are introduced based on the above technical methods for rapid detection of foodborne pathogenic bacteria. The paper also discusses the limitations of existing methods and their advantages and future development direction, to form an overall understanding of the detection methods, and for point-of-care testing (POCT) applications to accurately and rapidly diagnose and control diseases.